I Vote for the LIGHT One--More Payload! - Dow Chemical Company (1946)
Color print advertisement for Dowmetal, a magnesium alloy manufactured and sold by the Dow Chemical Company. The advertisement depicts two men examining model aircrafts, with the one man favoring the lighter one made from Dowmetal. The accompanying text details the use of Dowmetal in the aircraft industry and emphasizes the product's lightness and durability relative to other structural metals.
Keywords: Dow Chemical Company; Corporations; Chemical industry; Magnesium; Magnesium alloys; Magnesium industry and trade; Aircraft industry